VERIFICATION OF FLUID FLOW CALCULATIONS IN VORTEX CHAMBER SUPERCHARGERS - Rogovyi, A.; Роговой, А. С.; Роговий, А. С. (Харьковский национальный автомобильно-дорожный университет, 2016)
On the basis of numerical modeling (URANS) by means of specialized program complexes verification of fluid flow calculation in vortex chamber superchargers was carried out. It is determined that it is better to apply a model of incompressible liquid for calculations with the turbulence model, considering the streamline curvature and system rotation (SST curvature correction).
ВЕРИФИКАЦИЯ РАСЧЕТОВ ТЕЧЕНИЙ В ВИХРЕКАМЕРНЫХ НАГНЕТАТЕЛЯХ
ВЕРИФІКАЦІЯ РОЗРАХУНКІВ ТЕЧІЇ У ВИХОРОКАМЕРНИХ НАГНІТАЧАХ
Keywords: vortex chamber supercharger; numerical calculation; suction discharge; streamline curvature; correction; turbulence model; вихрекамерный нагнетатель; численные расчеты; расход всасывания; кривизна линий тока; поправка; модель турбулентности; вихорокамерний нагнітач; числові розрахунки; витрата всмоктування; кривизна ліній струму; поправка; модель турбулентності; 621.521